STRATEGI PENINGKATAN PELAYANAN PUBLIK - Ni Ketut Riani (Jurnal Inovasi Penelitian, 2021)
The challenge of the nation in the future in facing global competition in order to create a world-class bureaucracy in 2025, we must improve a lot, starting from reforming into ourselves. Departing from there was to inspire the author to write an article related to excellent service that must be given by every public servant is no exception in BPSDM Bali Province. Bali Province BPSDM Office as an institution that has certified A certification for the implementation of Pre-service Training, A is also for Leadership training both Pim 3 and Pim 4, while for Pim 2 Training is still at level B. Besides that BPSDM Bali Province in organizing Leadership Training is based on the thematic of tourism. This provided a stimulus to all prospective Pim participants from all over Indonesia to get the opportunity as participants. Departing from the accreditation owned by BPSDM Bali Province, all components involved in it must also be ensured to have quality that prioritizes excellent service quality. So, the question is .”.what is the quality of service at BPSDM Bali Province?” The answer is not yet optimal. This situation must be overcome immediately by finding a solution. Every complaint raised by the training alumni is a trigger for the institution to immediately find a way out. Increasing the competency of public service actors must be done for the realization of excellent service. The improvement referred to starting from the increase in cognitive (knowledge), phsycomotoric (skill) and affective (attitude) must continue to be done in accordance with their respective fields of work. Increasing competency can be done either through singakat worshop to the implementation of the education which takes longer according to the needs. The availability of hardware and software is no less important, especially during the era of the industrial revolution